RANCANG BANGUN SISTEM DISTRIBUSI HASIL PRODUKSI OBAT UNTUK MENJAMIN KUALITAS DALAM MENINGKATKAN PELAYANAN PELANGGAN - Turki Salim; Muhamad Yusup; Dewi Listiani Sukamto (UNIVERSITAS RAHARJA, 2020)
Pharmaceutical companies in Indonesia that are engaged in manufacturing currently continue to develop, they process medicinal ingredients into pharmaceuticals, such as tablets, syrup, capsules and others. At present the distribution and production management system of drugs is still semi-computerized, because it still uses Ms. Excel, which can cause file-to-file buildup, besides that it is possible that the data will be lost or damaged, and when searching for data, it takes a long time. To overcome this need to be built a system to process the drug distribution and production management system, to help companies more easily access drug data to computerized travel documents, so as to increase the effectiveness and time efficiency, and get maximum work results and data accuracy in data input in the relevant section. It certainly can be found with various methods that use penuls, starting from the use of uml to provide an overview of system design, then MySql as a data processing application in thedatabase, as a programming language using php.